2020
DOI: 10.1080/13543784.2020.1805733
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis – Ten promising therapeutic approaches in the current era of care

Abstract: The Institute for Clinical and Economic Review (ICER) is an independent non-profit research organization that evaluates medical evidence and convenes public deliberative bodies to help stakeholders interpret and apply evidence to improve patient outcomes and control costs. Through all its work, ICER seeks to help create a future in which collaborative efforts to move evidence into action provide the foundation for a more effective, efficient, and just health care system. More information about ICER is availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 242 publications
0
13
0
1
Order By: Relevance
“…In this case, lung 3D cultures, including precision-cut lung slices (PCLS) and hydrogels, have emerged as valuable tools for drug discovery of IPF (125)(126)(127). For instance, a new study demonstrated PCLS maintains the native lung microbiota and is a relevant in vitro model to study lung fibrosis and drug testing in a diseased tissue condition (128). We hope that more prospective studies will be conducted to evaluate the efficacy and safety of PCLS in treating IPF.…”
Section: D Models Of Ipf and Drug Discoverymentioning
confidence: 99%
“…In this case, lung 3D cultures, including precision-cut lung slices (PCLS) and hydrogels, have emerged as valuable tools for drug discovery of IPF (125)(126)(127). For instance, a new study demonstrated PCLS maintains the native lung microbiota and is a relevant in vitro model to study lung fibrosis and drug testing in a diseased tissue condition (128). We hope that more prospective studies will be conducted to evaluate the efficacy and safety of PCLS in treating IPF.…”
Section: D Models Of Ipf and Drug Discoverymentioning
confidence: 99%
“…Changes in antimicrobial treatment or in continuous antibiotic regimens are also made to prevent and reduce deterioration in lung function before the insurgence of pulmonary exacerbations [8,15,16]. Although the recent introduction of novel therapies targeting the defective CF transmembrane conductance regulator (CFTR) protein has transformed the landscape of CF [17,18], the antibiotic treatment of respiratory infections will remain the mainstay of CF therapy for the foreseeable future [19,20]. Accordingly, new treatment strategies for better management of acute and chronic episodes have been at the forefront of efforts to improve outcomes in CF.…”
Section: Of 16mentioning
confidence: 99%
“…30 Although there is no cure for cystic fibrosis, symptom-based therapies (such as antibiotics, bronchodilators, and mucus thinning medications) and CFTR modulating drugs have become the first-line treatments to relieve symptoms and reduce the risk of complications. 31 Currently, gene manipulation technologies and molecular targets are also being explored. The use of CRISPR/Cas-9 technology for genome editing has great potential, although it is in the early stages of development.…”
Section: Role In Gene Therapymentioning
confidence: 99%